Exploring the effectiveness of a rapid participatory method in mapping the role of agricultural biodiversity in local food systems to identify potential entry points to improve peoples' capabilities to be nutrition secure - Ahern, Molly B.; Raneri, Jessica Evelyn; Muro, P. de; Kennedy, G. (2016)
Vietnam has improved its food security situation at the price of losing traditional varieties adapted to local tastes and conditions due to increased production and use of high-yield crop varieties (mainly large scale mono-cropping). Decreased diversity of foods is a growing issue, and the existence of malnutrition in regions where staple crop production and food availability are sufficient highlights the necessity for a multidisciplinary approach to design interventions that target the four dimensions of food security - availability, access, stability and utilisation, of a diverse group of locally available nutritious foods.